Carving out a territory: Rhegion, Locri and the households and communities of the classical countryside. Issue 3 (26th May 2016) - Foxhall, Lin; Yoon, David
ABSTRACT: This paper investigates how people enacted multiple, alternative constructions of 'territory', using as a case study two neighbouring and often antagonistic ancient Greek city-states of southern Italy, Rhegion and Locri Epizephyrii, focusing primarily on the fifth–fourth centuriesbce . We ask how the everyday practices of the inhabitants dwelling in these rural hinterlands shaped their landscapes. Did their lived experience of the landscape map on to the boundaries and models of 'territory' presented in the urban-focused written sources? We suggest that though the written sources provide a useful overall context, it is more difficult to connect particular incidents directly with specific archaeological or landscape features. Applying Roman, or modern, concepts of boundaries and borders in this period may be anachronistic. Sovereignty of the urban centres, and even of the most powerful regional rulers, over the lands in the border zone between classical Rhegion and Locri largely appears constrained and patchy.